Fazer da queda um passo de dança: a intrincada coreografia neural do ato de dançar e seu potencial na reabilitação de pessoas com Parkinson - TEXEIRA, Nathália Oliveira (2024)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by the loss of dopaminergic neurons in the substantia nigra. Dance involves highly developed sensorimotor control, and many theories advocate its beneficial effects in neurodegenerative conditions. By drawing a parallel between the areas of the brain activated by dance and those affected by PD, we can understand the growing interest in dance as an adjuvant therapy. A robust body of evidence, based on extensive neural stimulation, points to the benefits of its practice on brain health in aging and neurodegenerative conditions, with various mechanisms elucidated in humans and animal models, for example, changes in the expression of neurotrophins, epigenetic and metabolic alterations. This work aims to discuss the neural basis of dance, with a focus on its therapeutic potential in the rehabilitation of people with PD.